Modification of simple algorithm to handle natural convection flows with zero-isothermal compressibility - Asako, Yutaka (Pergamon-Elsevier Science Ltd, 2017)
The conventional SIMPLE algorithm for the pressure–velocity coupling has been adopted by many commercial and non-commercial CFD codes. It encounters convergence problem when it is used to solve unsteady natural convection flows with zero-isothermal compressibility. In this paper, a modified version of this algorithm is proposed to remedy this drawback. The modification includes updating of the density at each time step based on its value at the previous time step to satisfy the continuity equation. As an example of utilizing the modified SIMPLE algorithm, the unsteady natural convection in a rectangular cavity with isothermal vertical walls and adiabatic horizontal walls was computed. Physically consistent results were obtained.